2023
DOI: 10.1001/jamanetworkopen.2023.18031
|View full text |Cite
|
Sign up to set email alerts
|

Key Components of Antenatal Lifestyle Interventions to Optimize Gestational Weight Gain

Abstract: ImportanceRandomized clinical trials have found that antenatal lifestyle interventions optimize gestational weight gain (GWG) and pregnancy outcomes. However, key components of successful interventions for implementation have not been systematically identified.ObjectiveTo evaluate intervention components using the Template for Intervention Description and Replication (TIDieR) framework to inform implementation of antenatal lifestyle interventions in routine antenatal care.Data SourcesIncluded studies were draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 142 publications
(1,805 reference statements)
0
1
0
Order By: Relevance
“…As an effectiveness trial, we apply the broadest eligibility criteria to enhance generalizability: Evidence shows that starting an intervention early in pregnancy has the greatest impact on pregnancy outcomes and GWG [47,48]. However, many home visiting programs rely on several steps to occur before services can begin, i.e., entry in prenatal care, referrals from clinic, screening by outside agency for eligibility, and outreach by home visiting program.…”
Section: Participant Eligibilitymentioning
confidence: 99%
“…As an effectiveness trial, we apply the broadest eligibility criteria to enhance generalizability: Evidence shows that starting an intervention early in pregnancy has the greatest impact on pregnancy outcomes and GWG [47,48]. However, many home visiting programs rely on several steps to occur before services can begin, i.e., entry in prenatal care, referrals from clinic, screening by outside agency for eligibility, and outreach by home visiting program.…”
Section: Participant Eligibilitymentioning
confidence: 99%
“…Systematic review evidence for the optimal dose of health coaching for obesity and type 2 diabetes interventions has identified that on average, 12-15 sessions of 35-40 min across 7-9 months are used in practice [31]. Moreover, a recent systematic review has identified six or more sessions as optimal in efficacious antenatal lifestyle interventions [32]. Given the emerging best practice guidelines for the dose of lifestyle interventions during pregnancy, further investigation into the optimal number of calls and gestational age for enrolment in the GHiP program is warranted.…”
Section: Program Engagementmentioning
confidence: 99%
“…According to the National Academy of Medicine (NAM) report in 2009, GWG associated with the lowest risk of adverse maternal and neonatal health outcomes is dependent on pre-gravid BMI [ 5 , 6 ]. Programs during pregnancy centered around diet, which include individual-level considerations for dietary intake and eating behaviors, have been shown to be the most effective interventions to reduce GWG [ 7 , 8 ]. As excess GWG is associated with more energy intake compared with energy expenditure [ 9 , 10 , 11 , 12 ], it is imperative to understand how eating behaviors contribute to GWG to advance effective program strategies to achieve the recommended GWG.…”
Section: Introductionmentioning
confidence: 99%